Colonization and local agreements in the consolidation of the Saraguro peasant livestock system in the Southern Ecuadorian Amazon - Buitrón Cañadas, Viviana Marcela (2017)
This article analyzes the role of different actors in the spatial configuration of the Saraguro colonization in the Southern Ecuadorian Amazon and the land use changes that occurred due to peasant productive activities. Semi-structured interviews with key informants about the local history and the context of colonization were conducted. Additionally, a land use analysis was performed for the years 1986, 2000 and 2010. The results point to the importance of agreements between local actors, as the saraguro colonists advanced from their original settlements in the Andes toward the Amazon, and show how colonization caused forest loss in favor of other uses, especially pastures. These findings suggest that through the search for land and the increasingly intensive use of land, the Saraguros were able to reproduce their Andean peasant livestock system in this area of the Amazon.